Jak w unii za piecem. Innowacje językowe w polskich, brytyjskich i niemieckich artykułach prasowych na temat referendum w sprawie członkostwa Wielkiej Brytanii w Unii Europejskiej - Miller, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The notion of linguistic innovation or neologism includes new lexical items as well as existing words or phrases whose meaning has been altered. Based on the classifications of neologisms proposed by Stanisław Grabias [1981], Stanisław Bąba [1986, 1989] and Gabriela Dziamska-Lenart [2004], the purpose of this paper is to present various types of linguistic innovations on the morphological and phraseological level. They are analysed in terms of structure, meaning and pragmatic purpose in texts. Particular attention is paid to lexical blends which encompass both word blends (i.e. portmanteau words) as well as idiom blends, i.e. blends of an idiom with a word or a combination of two idioms. The data analysed comes from articles published in popular Polish („Polityka”), British („The Economist”) and German („Der Spiegel”) weekly magazines shortly before and directly after the Brexit referendum. As the analysis shows, linguistic innovations mostly occur in press headlines especially in British texts. Apart from numerous idiom blends there are various examples of pun-like blends based on well-known quotations from popular culture. The main purpose of the analysed new lexical items is to attract the attention of the reader, to express the attitude of the author towards the entities described and thus to convey positive or negative valuations, to build a close relation between the author and the reader and to cause humorous effects.